Triphenylphosphonium-functionalized BODIPY derivatives for mitochondria-targeted cell imaging and fluorescence turn-on sensing with protein selectivity. (December 2022) - Mai, Duy Khuong; Badon, Isabel Wen; Lim, Jong Min; Vales, Temmy Pegarro; Kim, Chanwoo; Yang, Jaesung; Lee, Joomin; Kim, Ho-Joong
Abstract: Triphenylphosphonium (TPP) cations endow fluorophores with improved hydrophilicities and mitochondria targeting abilities. Evidently, the number of cationic moieties can influence the behavior of fluorophores in different environments. Two water-soluble BODIPY fluorophores, 3TPP and 5TPP, were constructed with three and five TPP groups, respectively, in their structure. Both showed maximum absorption and emission at 640–700 nm wavelengths; however, 5TPP showed a fluorescence quantum yield 10 times higher than that of 3TPP in an aqueous medium, highlighting the beneficial effect of two additional TPP groups on the photophysical properties. While both fluorophores showed excellent stabilities and mitochondrial imaging abilities with low cytotoxicities in HeLa and MCF-7 cells, 5TPP permeated into the mitochondria better than 3TPP . Interestingly, 5TPP demonstrated a 90-fold increase in "turn-on" fluorescence in the presence of bovine serum albumin (BSA) in relation to that of four other proteins (i.e., lysozyme, esterase, transferrin, and fibrinogen). Notably, the fluorescence intensity of 5TPP increased with increasing BSA concentration. The present work is the first report on BODIPY sensors with multiple bulky cationic moieties and provides insights on the applicability of 5TPP as a novel biomaterial for mitochondrion tracking and light-up fluorescence protein sensing. Highlights: BODIPY-based fluorophores, 3TPP and 5TPP, were conjugated with three and five (triphenylphosphonium) TPP groups, respectively. Both fluorophores showed excellent photostabilities and mitochondrial imaging abilities with low cytotoxicities in HeLa and MCF-7 cells. 5TPP exhibited a 90-fold increase in "turn-on" fluorescence in the presence of bovine serum albumin (BSA) with respect to that of four other proteins (i.e., lysozyme, esterase, transferrin, and fibrinogen).